Quack quack : these baby animals can't wait to meet you. (Baby touch and feel, 2004)
With touch and feel textures and rollicking rhymes to read, this book of cute baby animals makes a perfect gift for baby! Featuring a different texture on each page, this adorable book will stimulate your child's senses and encourage their imagination.